Validation: Knowledge- and Text-Based Monitoring During Reading. Issue 5 (18th August 2018) - van Moort, Marianne L.; Koornneef, Arnout; van den Broek, Paul W.
ABSTRACT: To create a coherent and correct mental representation of a text, readers must validate incoming information; they must monitor information for consistency with the preceding text and their background knowledge. The current study aims to contrast text- and knowledge-based monitoring to investigate their unique influences on processing and whether validation is passive or reader-initiated. Therefore, we collected reading times in a self-paced experiment using expository texts containing information that conflicts with either the preceding text or readers' background knowledge. Results show that text- and knowledge-based monitoring have different time courses and that working memory affects only knowledge-based monitoring. Furthermore, our results suggest that validation could occur at different levels of processing and perhaps draw on different mixes of passive and reader-initiated processes. These results contribute to our understanding of monitoring during reading and of how different sources of information can influence such monitoring.